On-Board Video-Evaluation Algorithm of Transverse Safety Clearance for Ahead Road-Vehicle - Yashina, Marina V.; Mokhov, Alexey I.; Belova, Maria A.; Kostsov, Alexey V.; Pospelov, Pavel I. (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Traffic flows are becoming more intense over time as a result of global automobilization. Road transport specialists are developing and analyzing different approaches to control traffic, to design and to build new highways. Decreasing total amount of accidents and congestion avoidance on a road are the main goals of this research. General traffic flow features and car localization are the most important types of data to be obtained, processed and analyzed in modern conditions as cars are highly maneuverable. Proper usage of this data allows building new high-quality traffic control systems taking in account all of its significant features. We have developed a system for video-processing from camera fixed on car torpedo. Research presented in this paper suggests an algorithm of transverse safety clearance evaluation by analyzing a video from vehicle on-board camera.